Obtaining and Conversion of Energy in Open Systems - L. I. Gretchikhin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
The paper considers conditions required for creation of open energy systems. Coefficient of energy obtaining and its conversion is more than one in such systems because environmental energy ingress is not taken into account. It is shown that in active environment conversion of energy from one type into another one takes place without any work expense, in other words this process is going on directly.